REVIEW ARTICLE: Cortical control of eye and head movements: integration of movements and percepts - Longtang Chen, L.; Tehovnik, Edward J. (The European journal of neuroscience, 2007)
The cortical control of eye movements is well known. It remains unclear, however, as to how the eye fields of the frontal lobes generate and coordinate eye and head movements. Here, we review the recent advances in electrical stimulation studies and evaluate relevant models. As electrical stimulation is conducted in head‐unrestrained, behaving subjects with the evoked eye and head movements sometimes being indistinguishable from natural gaze shifts, a pertinent question becomes whether these movements are evoked by motor programs or sensory percepts. Recent stimulation studies in the visual cortex and the eye fields of the frontal lobes have begun to bring both possibilities to light. In addition, cognitive variables often interact with behavioral states that can affect movements evoked by stimulation. Identifying and controlling these variables are critical to our understanding of experimental results based on electrically evoked movements. This understanding is needed before one can draw inferences from such results to elucidate the neural mechanisms underlying natural and complex movements.